Google Docs in Undergraduate online Composition Class: Investigating Learning Styles’ Impact on Writing Corrective Feedback - Zaky, Hany (Asian Journal of Interdisciplinary Research, 2021)
Google Docs, as a collaborative online writing tool in Higher Education, facilitates and enhances the Composition pedagogical practices in face-to-face and virtual classes. The purpose of this quantitative study is to investigate the students’ learning styles’ impact on their Peer Assessment using Google Docs. Participants included 149 Composition students in a Public Health College of a private university in New York City. The statistical findings of this study revealed that students’ learning skills in online writing classes could drive their perceptions of using Google Docs as a Peer Assessment Writing tool. These findings highlight the high correlation between students’ desire to interact after writing in English and their perceptions of using Google Docs as a collaborative writing tool. The findings also revealed statistically significant relationships between students’ perceptions of using Google Docs and their preferences of receiving feedback in different language areas. An increase in students’ perception of receiving feedback on their grammar, the flow of ideas, mechanics, quality of ideas, and Vocabulary, in that order, strongly led to an increase in their perceptions of using Google Docs. However, the findings indicate that there was no statistically significant linear relationship between students’ perceptions of their technical skills and their perceptions of using Google Docs in their online writing classes. Median Google Docs’s perceptions of males and females were not statistically different. There were no statistically significant differences in students’ Perceptions of Using Google Docs across the various age groups.